Relationship between time-varying status of reflux esophagitis and Helicobacter pylori and progression to long-segment Barrett’s esophagus: time-dependent Cox proportional-hazards analysis - Genki Usui; Tomohiro Shinozaki; Toyohisa Jinno; Kazutoshi Fujibayashi; Teppei Morikawa; Toshiaki Gunji; Nobuyuki Matsuhashi (BMC Gastroenterology, 2020)
Abstract Background Reflux esophagitis (RE) and absence of Helicobacter pylori (non-H. pylori) are considered to be associated with the progression to long-segment Barrett’s esophagus (LSBE). However, it is difficult to assess this association because RE and H. pylori status can change during follow-up. Additionally, the association between H. pylori eradication and LSBE remains unclear. Methods A total of 11,493 asymptomatic Japanese subjects who underwent medical check-ups and were endoscopically diagnosed with short-segment Barrett’s esophagus (SSBE) between May 2006 and December 2015 were enrolled. The hazards of progression to LSBE were compared between time-varying RE and H. pylori infection/eradication by time-dependent multivariable Cox proportional hazards models. Results A total of 7637 subjects who underwent additional medical check-ups after being diagnosed with endoscopic SSBE were analyzed. Subjects with RE and without current/past H. pylori infection were strongly associated with a higher rate of progression to LSBE (adjusted hazard ratio [HR]: 7.17, 95% confidence interval [CI]: 2.48–20.73, p < 0.001 for RE and non-H. pylori vs. non-RE and H. pylori groups). Subjects with H. pylori had a lower rate of progression to LSBE (adjusted HR: 0.48, 95% CI: 0.22–1.07, p = 0.07 for H. pylori vs. non-H. pylori). Hazards of progression to LSBE were still lower in the H. pylori eradication group than that of the non-H. pylori group (adjusted HR: 0.51, 95% CI: 0.18–1.46, p = 0.21). Conclusions RE and non-H. pylori were associated with the progression to LSBE, considering the changes in exposures. H. pylori infection was associated with the prevention of the development of LSBE irrespective of RE. The environment preventive of the development of LSBE persists for at least a few years after H. pylori eradication.